Preparation method of tetrahedral CBN (cubic boron nitride)
By using Li8SiN4 as a catalyst in CBN preparation, tetrahedral CBN is synthesized under high temperature and high pressure, and multi-step chemical treatment is carried out, the problems of crystal dysplasia and complex preparation in existing CBN preparation are solved, and high-quality and low-cost tetrahedral CBN preparation are achieved.
Patent Information
- Application Number
- CN202411520490.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-14
AI Technical Summary
In the existing CBN preparation methods, the crystals are incomplete, have many defects, irregular shapes, and the preparation method is complex and costly, which cannot meet the requirements of abrasives.
Li8SiN4 is used as catalyst to synthesize tetrahedral CBN under high temperature and high pressure, and tetrahedral CBN crystals with smooth surface, few defects and sharp edges are obtained.
It has achieved high conversion and good quality CBN single crystal preparation, with improved crystal equal-cell shape ratio and sharp edges and angles. It is suitable for grinding materials, and the preparation method is simple and cost-effective.
Smart Images

Figure CN119608036A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of CBN, and in particular relates to a method for preparing tetrahedron CBN. Background Art
[0002] Cubic boron nitride (CBN) is a new type of artificially synthesized material developed in the 1950s. It has high hardness and good wear resistance and is widely used in the machining industry. Cubic boron nitride is synthesized from hexagonal boron nitride and catalyst under high temperature and high pressure. It is another new product that has emerged after the advent of artificial diamond. The existing preparation method uses composite nitrogen boride of alkali metals and alkaline earth metals as a catalyst to obtain CBN crystals with a high conversion rate, but contains more flaky crystals, and the crystals are incompletely developed, have many defects, and have poor crystal shape, which cannot meet the requirements of abrasives. In addition, the preparation method is complicated and costly. Therefore, it is very necessary to provide a method for preparing tetrahedral CBN with a simple method, regular shape, smooth surface, few defects, and sharp edges. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and to provide a method for preparing tetrahedral CBN which is simple, regular in shape, smooth in surface, few in defects and sharp in edges and corners.
[0004] The object of the present invention is achieved in this way: a method for preparing tetrahedral CBN, wherein the method comprises the following steps: Step 1: Catalyst preparation: The catalyst is a Li-based composite nitride; Step 2: Mixing: 0.5-7.0wt% of catalyst and 21-30wt% of BN material; Step 3: Sieving and pressing: Sieve the material from the previous step, weigh the powder of a set mass and put it into a round mold, and pre-press it into a round bar on a hydraulic press; Step 4: Assembling: The round rods formed in the previous step are loaded into the pyrophyllite block mechanism to form a synthetic block; Step 5: High temperature and high pressure synthesis: the synthesis block formed in the previous step is loaded into the high pressure chamber of the six-sided top press to obtain a high pressure synthesis block sample; Step 6: Crystallization treatment: After hot pressing and sintering, the obtained boron nitride sintered body is placed in a specific high-temperature furnace equipment, and then heated at a set crystallization temperature and pressure to promote the crystal phase transformation of the boron nitride raw material; Step 7: Insulation and cooling: After reaching the crystallization temperature, it is kept for a period of time, which is called the insulation stage. After the insulation is completed, the cooling rate is controlled to stably generate cubic boron nitride crystals from the boron nitride raw materials; Step 8: Synthetic baseball mill: The crystallized cubic boron nitride block sample is crushed by tapping and then ball milled; Step 9: First step of chemical treatment: Then put the ball milled material in a container, add deionized water and boil it, stop heating after 30 minutes, then collect the CBN at the bottom of the container and dry it; then put the dried CBN into a strong alkaline solution and boil it for 20-40 minutes, and then rinse it with deionized water for 3-5 times; Step 10: Second chemical treatment: After the above steps, collect the CBN at the bottom of the container and boil it in a strong acid solution for 20-40 minutes, then rinse it repeatedly with deionized water; Step 11: Drying treatment: Then put the obtained CBN into an oven at 130-160°C and dry it for 4 hours to obtain a CBN crystal; Step 12: Shaping, screening, testing, packaging and microscopic examination.
[0005] The Li-based composite nitride used as the catalyst in step 1 is Li8SiN4.
[0006] The BN in step 2 is pretreated BN, whose GI value is 3.0 and the purity of the HBN material reaches more than 99%.
[0007] The density of the pre-pressed round bar in step 3 is 1.3-1.9 g / cm³.
[0008] In the pyrophyllite block mechanism in step 4, pyrophyllite is used as a sealing and pressure transmission medium, and tubular graphite is used as a heating element.
[0009] The high temperature and high pressure synthesis conditions in step 5 are: synthesis pressure of 4.5~5.0GPa, synthesis temperature of 1500~1800℃, and synthesis time of 5~8min; the high temperature and high pressure temperature and pressure measurement methods are specifically: temperature measurement with Pt30%Rh-Pt6%Rh thermocouple under high pressure and pressure calibration with fixed phase change points of Bi, T1 and Ba at room temperature.
[0010] The six-sided top press in step 5 adopts a DS-029C type 6×8×106 six-sided top ultra-high pressure device.
[0011] The crystallization treatment in step 6 is specifically as follows: after hot pressing and sintering, the obtained boron nitride sintered body is placed in a specific high-temperature furnace equipment, and then slowly heated to 1000-1850°C under the protection of nitrogen at 0.5 atmospheres and a flow rate of 20 mL / min for heating treatment to promote the crystal phase transformation of the boron nitride raw material; the insulation and cooling in step 7 are specifically as follows: after reaching the crystallization temperature, it is maintained for 2 hours, which is called the insulation stage. After the insulation is completed, the high-temperature furnace equipment is turned off when the temperature is lowered to 800°C by controlling the cooling rate until the high-temperature furnace equipment is cooled to room temperature.
[0012] The purpose of the chemical treatment in steps 9-10 is to remove residual catalyst, graphite and unconverted HBN.
[0013] The screening in step 12 is performed using a standard vibrating screen; the color of the CBN single crystal is observed using OM, the surface morphology of the CBN single crystal is observed using SEM, and the static pressure strength of the CBN single crystal is measured using a strength tester.
[0014] The beneficial effects of the present invention are as follows: the present invention is a method for preparing tetrahedral CBN. In use, the present invention adds Li8SiN4 as a catalyst in the catalyst system of Li-based composite nitrogen boride within the range of 4.5-5.0GPa and 1500-1800°C, effectively avoiding the disadvantage that the compound and the alloy are difficult to disperse evenly and thus the conversion rate is reduced, and a crystal with high conversion rate and good quality is obtained, and a shiny brown transparent CBN single crystal is obtained. After adding Li8SiN4, the percentage of the obtained iso-area CBN crystal is significantly increased, and except for some truncated octahedrons, most of them are truncated tetrahedral crystals with sharp edges and corners, and the crystal faces are dense and smooth. The CBN prepared by the preparation method of the present invention is an iso-area crystal with regular single crystal growth shape, smooth surface, few defects and sharp edges and corners. The composite nitride Li8SiN4 is added to make the underdeveloped CBN The sharpness of the edges and corners of the crystal morphology are significantly improved, the equal-area crystals are generally increased, the truncated tetrahedral crystals are in the majority, and the crystals are fully developed and have sharp edges and corners, which are more suitable for use as grinding materials. The present invention has the advantages of simple method, regular shape, smooth surface, few defects and sharp edges and corners. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a high pressure assembly diagram of the tetrahedral CBN preparation method of the present invention.
[0016] Figure 2 The present invention is a process flow chart of hexagonal boron nitride production in the method for preparing tetrahedral CBN.
[0017] Figure 3 It is a process flow chart of the method for preparing tetrahedral CBN of the present invention.
[0018] Figure 4 Schematic diagram of WBN-90 of the tetrahedral CBN preparation method of the present invention Figure 1 .
[0019] Figure 5 Schematic diagram of WBN-90 of the tetrahedral CBN preparation method of the present invention Figure 2 .
[0020] Figure 6 Schematic diagram of WBN-90 of the tetrahedral CBN preparation method of the present invention Figure 3 .
[0021] Figure 7 Schematic diagram of WBN80T of the tetrahedral CBN preparation method of the present invention.
[0022] Figure 8 Schematic diagram of SED of WBN80T in the method for preparing tetrahedral CBN of the present invention.
[0023] Fig. 9 Schematic diagram of WBN80 of the tetrahedral CBN preparation method of the present invention.
[0024] Fig.10 Schematic diagram of SED of WBN80 in the method for preparing tetrahedral CBN of the present invention.
[0025] Fig.11 Schematic diagram of WBN30 of the tetrahedral CBN preparation method of the present invention.
[0026] Fig.12 Schematic diagram of SED of WBN30 in the method for preparing tetrahedral CBN of the present invention.
[0027] Fig.13 Schematic diagram of WBN50 of the method for preparing tetrahedral CBN of the present invention.
[0028] In the figure: A, sample B, graphite sheet C, titanium sheet D, conductive circle E, pyrophyllite F, graphite tube. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the accompanying drawings. Example
[0030] like Figure 1-13 As shown, a method for preparing tetrahedral CBN, the method comprising the following steps: Step 1: Catalyst preparation: The catalyst is a Li-based composite (in actual use, alkali metals, alkaline earth metals, tin, lead, antimony and their nitrides can also be used as catalysts); Step 2: Mixing: 0.5wt% of catalyst and 21wt% of BN material; Step 3: Sieving and pressing: Sieve the material from the previous step, weigh the powder of a set mass and put it into a round mold, and pre-press it into a round bar on a hydraulic press; Step 4: Assembling: The round rod formed in the previous step is loaded into the pyrophyllite block mechanism to form a synthetic block; Step 5: High temperature and high pressure synthesis: Load the synthesis block formed in the previous step into the high pressure chamber of the six-sided top press, and wait until the high pressure synthesis block sample is obtained; Step 6: Crystallization treatment: After hot pressing and sintering, the obtained boron nitride sintered body is placed in a specific high-temperature furnace equipment, and then heated at a set crystallization temperature and pressure to promote the crystal phase transformation of the boron nitride raw material; Step 7: Insulation and cooling: After reaching the crystallization temperature, it is kept for a period of time, which is called the insulation stage. After the insulation is completed, the cooling rate is controlled to stably generate cubic boron nitride crystals from the boron nitride raw materials; Step 8: Synthetic baseball mill: The crystallized cubic boron nitride block sample is crushed by tapping and then ball milled; Step 9: First step of chemical treatment: Then put the ball milled material in a container, add deionized water and boil it, stop heating after 30 minutes, then collect the CBN at the bottom of the container and dry it; then put the dried CBN into a strong alkaline solution and boil it for 20 minutes, and then rinse it with deionized water for 3 times; Step 10: Second chemical treatment: After the above steps, collect the CBN at the bottom of the container and boil it in a strong acid solution for 20 minutes, then rinse it repeatedly with deionized water; Step 11: Drying treatment: The obtained CBN is then placed in an oven at 130°C and dried for 4 hours to obtain a CBN crystal; Step 12: Shaping, screening, testing, packaging and microscopic examination.
[0031] The invention discloses a method for preparing tetrahedral CBN. In use, the invention adds Li8SiN4 as a catalyst in a catalyst system of a Li-based composite nitrogen boride within the range of 4.5-5.0GPa and 1500-1800°C, effectively avoiding the disadvantage that it is difficult to evenly disperse compounds and alloys, resulting in a reduced conversion rate, thereby obtaining a crystal with high conversion rate and good quality, and obtaining a glossy brown transparent CBN single crystal. After adding Li8SiN4, the percentage of the obtained iso-area CBN crystal is significantly increased, and except for some truncated octahedrons, most of the crystals are truncated tetrahedral crystals with sharp edges and corners, and the crystal faces are dense and smooth. The CBN prepared by the preparation method of the invention is an iso-area crystal with a regular single crystal growth shape, a smooth surface, few defects, and sharp edges and corners. The composite nitride Li8SiN4 is added to make the underdeveloped CBN The sharpness of the edges and corners of the crystal morphology are significantly improved, the equal-area crystals are generally increased, the truncated tetrahedral crystals are in the majority, and the crystals are fully developed and have sharp edges and corners, which are more suitable for use as grinding materials. The present invention has the advantages of simple method, regular shape, smooth surface, few defects and sharp edges and corners. Example
[0032] like Figure 1-13 As shown, a method for preparing tetrahedral CBN, wherein the method comprises the following steps: Step 1: Catalyst preparation: The catalyst is a Li-based composite; Step 2: Mixing: 3.8wt% of catalyst and 25wt% of BN material; Step 3: Sieving and pressing: Sieve the material from the previous step, weigh the powder of a set mass and put it into a round mold, and pre-press it into a round bar on a hydraulic press; Step 4: Assembling: The round rod formed in the previous step is loaded into the pyrophyllite block mechanism to form a synthetic block; Step 5: High temperature and high pressure synthesis: Load the synthesis block formed in the previous step into the high pressure chamber of the six-sided top press, and wait until the high pressure synthesis block sample is obtained; Step 6: Crystallization treatment: After hot pressing and sintering, the obtained boron nitride sintered body is placed in a specific high-temperature furnace equipment, and then heated at a set crystallization temperature and pressure to promote the crystal phase transformation of the boron nitride raw material; Step 7: Insulation and cooling: After reaching the crystallization temperature, it is kept for a period of time, which is called the insulation stage. After the insulation is completed, the cooling rate is controlled to stably generate cubic boron nitride crystals from the boron nitride raw materials; Step 8: Synthetic baseball mill: The crystallized cubic boron nitride block sample is crushed by tapping and then ball milled; Step 9: First step of chemical treatment: Then put the ball milled material in a container, add deionized water and boil it, stop heating after 30 minutes, then collect the CBN at the bottom of the container and dry it; then put the dried CBN into a strong alkaline solution and boil it for 30 minutes, and then rinse it with deionized water 4 times; Step 10: Second chemical treatment: After the above steps, collect the CBN at the bottom of the container and boil it in a strong acid solution for 30 minutes, then rinse it repeatedly with deionized water; Step 11: Drying treatment: The obtained CBN is then placed in an oven at 145°C and dried for 4 hours to obtain a CBN crystal; Step 12: Shaping, screening, testing, packaging and microscopic examination.
[0033] In this embodiment, the effect of different Li8SiN4 addition amounts on the morphology of CBN crystals: Li8SiN4 was added to the catalyst system in different proportions to synthesize CBN crystals, and the morphology changed significantly. In the appropriate pressure and temperature region, when the Li8SiN4 addition amount was appropriate, the obtained CBN crystals were brown, the crystals were relatively complete, the crystal surfaces were smooth, there were no continuous crystals, and the equal-area shape ratio was greater than 80%. Table 1 lists the experimental conditions and experimental results.
[0034] Table 1 Experimental conditions and results of synthesizing CBN using Li8SiN4 as a catalyst additive Sample <![CDATA[Li8SiN4(wt%)]]> Temperature / (℃) Pressure / (GPa) CBN (wt%) Color of CBN 1 0 1530 4.60 21 Gold 2 0.5 1560 4.65 25 Amber 3 1.0 1600 4.65 29 Amber 4 2.0 1530 4.70 25 Brown 5 3.0 1580 4.75 36 Brown 6 3.8 1690 4.85 21 Dark brown 7 4.3 1580 4.60 23 Dark brown 8 4.8 1600 4.70 35 Dark brown 9 5.7 1640 4.85 25 Brown yellow 10 7.0 1700 4.85 30 Brown yellow The average results of a large number of experiments in the table show that the addition of Li8SiN4 slightly increases the conversion rate of HBN to CBN, and does not inhibit the conversion of HBN to CBN. The synthesized CBN crystal gradually changes from golden yellow to dark brown and then to brownish yellow with the addition of Li8SiN4, showing the difference in crystal growth environment. This difference in color and morphology may be due to the effect of adding Si on CBN growth and changes in synthesis conditions. However, pressure and temperature are roughly measured values, and the difference is not considered to be significant within the error range. When the temperature and pressure conditions are changed for samples with the same Si addition, the color of single-size grains does not change significantly, and the percentage of iso-area crystals does not increase significantly. Therefore, the influence of Li8SiN4 on the growth characteristics of CBN plays a major role. The CBN synthesized without adding Li8SiN4 has more flake crystals, incomplete crystal development, more defects, a large number of skeletal crystals and linked crystals, and irregular crystal shape. With the increase of the addition amount of composite nitride Li8SiN4, the crystal shape of CBN crystal is significantly improved, the percentage of isomorphous crystals is significantly increased, and the flake crystals are significantly reduced. When the addition amount of Li8SiN4 is small, the crystal morphology is slightly improved, the defects are slightly reduced, but there are still many linked crystals and skeletal crystals. Therefore, the improvement effect of a small amount of Li8SiN4 on the crystal morphology is not very obvious; when Li8SiN4 is added, the crystal morphology is slightly improved, the defects are slightly reduced, but the linked crystals and skeletal crystals are still large. When the addition amount increases, its effect on improving the crystal morphology is enhanced, the crystal defects are significantly reduced, the crystal isomorphism is good, and it shows a solid and heavy feeling; when the addition amount of Li8SiN4 reaches 3.8%, there are fewer lamellar crystals, except for a small amount of truncated octahedrons, most of them are truncated tetrahedrons with regular crystal shape, the crystal development is relatively complete, the crystal surface is dense and smooth, and there are fewer defects; thereafter, when the addition amount of Li8SiN4 increases, Luan crystals and secondary crystals appear, and the crystal shape becomes more complex; in summary, when the addition amount of Li8SiN4 changes from none to a small amount, from a small amount to an appropriate amount, and from an appropriate amount to a large amount, the crystal shape of the CBN crystal changes from irregular lamellar to isomorphic tetrahedrons and a small amount of isomorphic octahedrons to isomorphic Li crystals and secondary concatenated crystals; therefore, Li8SiN4 improves the supersaturation range and viscosity of the solution within a certain concentration range, allowing the crystal to be fully developed.
[0035] The invention discloses a method for preparing tetrahedral CBN. In use, the invention adds Li8SiN4 as a catalyst in a catalyst system of a Li-based composite nitrogen boride within the range of 4.5-5.0GPa and 1500-1800°C, effectively avoiding the disadvantage that it is difficult to evenly disperse compounds and alloys, resulting in a reduced conversion rate, thereby obtaining a crystal with high conversion rate and good quality, and obtaining a glossy brown transparent CBN single crystal. After adding Li8SiN4, the percentage of the obtained iso-area CBN crystal is significantly increased, and except for some truncated octahedrons, most of the crystals are truncated tetrahedral crystals with sharp edges and corners, and the crystal faces are dense and smooth. The CBN prepared by the preparation method of the invention is an iso-area crystal with a regular single crystal growth shape, a smooth surface, few defects, and sharp edges and corners. The composite nitride Li8SiN4 is added to make the underdeveloped CBN The sharpness of the edges and corners of the crystal morphology are significantly improved, the equal-area crystals are generally increased, the truncated tetrahedral crystals are in the majority, and the crystals are fully developed and have sharp edges and corners, which are more suitable for use as grinding materials. The present invention has the advantages of simple method, regular shape, smooth surface, few defects and sharp edges and corners. Example
[0036] like Figure 1-13 As shown, a method for preparing tetrahedral CBN, wherein the method comprises the following steps: Step 1: Catalyst preparation: The catalyst is a Li-based composite; Step 2: Mixing: 7.0 wt% of the catalyst and 30 wt% of the BN material; Step 3: Sieving and pressing: Sieve the material from the previous step, weigh the powder of a set mass and put it into a round mold, and pre-press it into a round bar on a hydraulic press; Step 4: Assembling: The round rod formed in the previous step is loaded into the pyrophyllite block mechanism to form a synthetic block; Step 5: High temperature and high pressure synthesis: Load the synthesis block formed in the previous step into the high pressure chamber of the six-sided top press, and wait until the high pressure synthesis block sample is obtained; Step 6: Crystallization treatment: After hot pressing and sintering, the obtained boron nitride sintered body is placed in a specific high-temperature furnace equipment, and then heated at a set crystallization temperature and pressure to promote the crystal phase transformation of the boron nitride raw material; Step 7: Insulation and cooling: After reaching the crystallization temperature, it is kept for a period of time, which is called the insulation stage. After the insulation is completed, the cooling rate is controlled to stably generate cubic boron nitride crystals from the boron nitride raw materials; Step 8: Synthetic baseball mill: The crystallized cubic boron nitride block sample is crushed by tapping and then ball milled; Step 9: First step of chemical treatment: Then put the ball milled material in a container, add deionized water and boil it, stop heating after 30 minutes, then collect the CBN at the bottom of the container and dry it; then put the dried CBN into a strong alkaline solution and boil it for 40 minutes, and then rinse it with deionized water for 5 times; Step 10: Second chemical treatment: After the above steps, collect the CBN at the bottom of the container and boil it in a strong acid solution for 40 minutes, then rinse it repeatedly with deionized water; Step 11: Drying treatment: The obtained CBN is then placed in an oven at 160°C and dried for 4 hours to obtain a CBN crystal; Step 12: Shaping, screening, testing, packaging and microscopic examination.
[0037] The invention discloses a method for preparing tetrahedral CBN. In use, the invention adds Li8SiN4 as a catalyst in a catalyst system of a Li-based composite nitrogen boride within the range of 4.5-5.0GPa and 1500-1800°C, effectively avoiding the disadvantage that it is difficult to evenly disperse compounds and alloys, resulting in a reduced conversion rate, thereby obtaining a crystal with high conversion rate and good quality, and obtaining a glossy brown transparent CBN single crystal. After adding Li8SiN4, the percentage of the obtained iso-area CBN crystal is significantly increased, and except for some truncated octahedrons, most of the crystals are truncated tetrahedral crystals with sharp edges and corners, and the crystal faces are dense and smooth. The CBN prepared by the preparation method of the invention is an iso-area crystal with a regular single crystal growth shape, a smooth surface, few defects, and sharp edges and corners. The composite nitride Li8SiN4 is added to make the underdeveloped CBN The sharpness of the edges and corners of the crystal morphology are significantly improved, the equal-area crystals are generally increased, the truncated tetrahedral crystals are in the majority, and the crystals are fully developed and have sharp edges and corners, which are more suitable for use as grinding materials. The present invention has the advantages of simple method, regular shape, smooth surface, few defects and sharp edges and corners.
Claims
1. A method for preparing tetrahedral CBN, characterized in that: The method comprises the following steps: Step 1: Catalyst preparation: The catalyst is a Li-based composite nitride; Step 2: Mixing: 0.5-7.0wt% of catalyst and 21-30wt% of BN material; Step 3: Sieving and pressing: Sieve the material from the previous step, weigh the powder of a set mass and put it into a round mold, and pre-press it into a round bar on a hydraulic press; Step 4: Assembling: The round rod formed in the previous step is loaded into the pyrophyllite block mechanism to form a synthetic block; Step 5: High temperature and high pressure synthesis: the synthesis block prepared in the previous step is loaded into the high pressure chamber of the six-sided top press to obtain a high pressure synthesis block sample; Step 6: Crystallization treatment: After hot pressing and sintering, the obtained boron nitride sintered body is placed in a specific high-temperature furnace equipment, and then heated at a set crystallization temperature and pressure to promote the crystal phase transformation of the boron nitride raw material; Step 7: Insulation and cooling: After reaching the crystallization temperature, it is kept for a period of time, which is called the insulation stage. After the insulation is completed, the cooling rate is controlled to stably generate cubic boron nitride crystals from the boron nitride raw materials; Step 8: Synthetic baseball mill: The crystallized cubic boron nitride block sample is crushed by tapping and then ball milled; Step 9: First step of chemical treatment: Then put the ball milled material in a container, add deionized water and boil it, stop heating after 30 minutes, then collect the CBN at the bottom of the container and dry it; then put the dried CBN into a strong alkaline solution and boil it for 20-40 minutes, and then rinse it with deionized water for 3-5 times; Step 10: Second chemical treatment: After the above steps, collect the CBN at the bottom of the container and boil it in a strong acid solution for 20-40 minutes, then rinse it repeatedly with deionized water; Step 11: Drying treatment: Then put the obtained CBN into an oven at 130-160°C and dry it for 4 hours to obtain a CBN crystal; Step 12: Shaping, screening, testing, packaging and microscopic examination.
2. The method for preparing tetrahedral CBN according to claim 1, characterized in that: The Li-based composite nitride used as the catalyst in step 1 is Li8SiN4.
3. The method for preparing tetrahedral CBN according to claim 1, characterized in that: The BN in step 2 is pretreated BN, whose GI value is 3.0 and the purity of the HBN material reaches more than 99%.
4. The method for preparing tetrahedral CBN according to claim 1, characterized in that: The density of the pre-pressed round bar in step 3 is 1.3-1.9 g / cm³.
5. The method for preparing tetrahedral CBN according to claim 1, characterized in that: In the pyrophyllite block mechanism in step 4, pyrophyllite is used as a sealing and pressure transmission medium, and tubular graphite is used as a heating element.
6. The method for preparing tetrahedral CBN according to claim 1, characterized in that: The high temperature and high pressure synthesis conditions in step 5 are: synthesis pressure of 4.5~5.0GPa, synthesis temperature of 1500~1800℃, and synthesis time of 5~8min; the high temperature and high pressure temperature and pressure measurement methods are specifically: temperature measurement with Pt30%Rh-Pt6%Rh thermocouple under high pressure and pressure calibration with fixed phase change points of Bi, T1 and Ba at room temperature.
7. The method for preparing tetrahedral CBN according to claim 6, characterized in that: The six-sided top press in step 5 adopts a DS-029C type 6×8×106 six-sided top ultra-high pressure device.
8. The method for preparing tetrahedral CBN according to claim 1, characterized in that: The crystallization treatment in step 6 is specifically as follows: after hot pressing and sintering, the obtained boron nitride sintered body is placed in a specific high-temperature furnace equipment, and then slowly heated to 1000-1850°C under the protection of nitrogen at 0.5 atmospheres and a flow rate of 20 mL / min for heating treatment to promote the crystal phase transformation of the boron nitride raw material; the insulation and cooling in step 7 are specifically as follows: after reaching the crystallization temperature, it is maintained for 2 hours, which is called the insulation stage. After the insulation is completed, the high-temperature furnace equipment is turned off when the temperature is lowered to 800°C by controlling the cooling rate until the high-temperature furnace equipment is cooled to room temperature.
9. The method for preparing tetrahedral CBN according to claim 1, characterized in that: The purpose of the chemical treatment in steps 9-10 is to remove residual catalyst, graphite and unconverted HBN.
10. The method for preparing tetrahedral CBN according to claim 1, characterized in that: The screening in step 12 is performed using a standard vibrating screen; the color of the CBN single crystal is observed using OM, the surface morphology of the CBN single crystal is observed using SEM, and the static pressure strength of the CBN single crystal is measured using a strength tester.